2015
DOI: 10.1007/s10936-015-9375-1
|View full text |Cite
|
Sign up to set email alerts
|

Universal Restrictions on Syllable Structure: Evidence From Mandarin Chinese

Abstract: Across languages, certain onset clusters are systematically preferred (e.g., [Formula: see text], "[Formula: see text]" indicates preference), and speakers extend these preferences even to onsets that are unattested in their language. All such demonstrations, however, come from cluster-rich languages, so the observed preferences could reflect not universal linguistic restrictions but lexical analogy. To address this possibility, here, we turn to Mandarin Chinese-a cluster-poor language. We reasoned that, if pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…These results significantly expand on and develop the arguments presented in previous work on sonority projection (Berent 2008;Berent et al 2009Berent et al , 2007Berent et al , 2008Zhao & Berent 2015;Lennertz & Berent 2015;Tamási & Berent 2014;Berent et al 2012Berent et al , 2011Daland et al 2011;Hayes 2011;Ren et al 2010;Davidson 2006). This paper does not dispute the findings presented by Hayes (2011) and (Daland et al 2011).…”
Section: General Discussion and Conclusionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results significantly expand on and develop the arguments presented in previous work on sonority projection (Berent 2008;Berent et al 2009Berent et al , 2007Berent et al , 2008Zhao & Berent 2015;Lennertz & Berent 2015;Tamási & Berent 2014;Berent et al 2012Berent et al , 2011Daland et al 2011;Hayes 2011;Ren et al 2010;Davidson 2006). This paper does not dispute the findings presented by Hayes (2011) and (Daland et al 2011).…”
Section: General Discussion and Conclusionsupporting
confidence: 87%
“…(1 Recent studies employing a variety of behavioural tasks across multiple languages have consistently found that the SSP is active in speakers' grammars (Berent 2008;Berent et al 2009Berent et al , 2007Berent et al , 2008Zhao & Berent 2015;Lennertz & Berent 2015;Tamási & Berent 2014;Berent et al 2012Berent et al , 2011Daland et al 2011;Ren et al 2010;Davidson 2006). Because the effects of SSP are found for novel clusters that are unobserved in the speakers' language input, these effects have been termed sonority projection (see also Hayes 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the literature provides no extensive and clear-cut answers. Critically, phonological universals such as sonority have not been a clear focus of study, except in the case of research into speech production and perception, despite the fact that it might be a credible candidate that co-contributes with or even compensates for statistical properties in silent reading (e.g., in speech perception in English, Russian, and Korean, Berent et al, 2007Berent et al, , 2008Berent et al, , 2011Berent et al, , 2012ain Spanish, Berent et al, 2012b;in French, Maïonchi-Pino et al, 2013; in Mandarin Chinese, Zhao and Berent, 2016). Given that sensitivity to sonority-based constraints might be available at an early age and independently of linguistic experience and that it might also contribute to language acquisition (e.g., Gómez et al, 2014), current studies should examine how and when phonological sonority-based markedness impacts reading.…”
Section: Introductionmentioning
confidence: 99%
“…Winters (2001) showed that English speakers preferred consonant-consonant metathesis when the perceptibility of the two consonants improved, suggesting that syllable contact law and sonority may serve as a cover constraint for perceptibility (Henke et al, 2012). In addition, Berent and colleagues have shown a robust tendency for language users (independent of language background) to be sensitive to typological generalizations about sonority, even when there is only scant evidence for those generalizations in the native language (Berent & Lennertz, 2010; Berent, Lennertz, Smolensky, & Vaknin-Nusbaum, 2009; Berent et al, 2010; Zhao & Berent, 2015). While Berent et al (2009) found that English speakers prefer nasal-stop clusters to stop-nasal clusters, a seemingly contradictory result from Experiment 4, the clusters used in Berent et al (2009) were illegal in English, while the consonants used in the present study crossed a syllable boundary and were therefore legal in English.…”
Section: Discussionmentioning
confidence: 99%